The Relationship between Dental Caries and Oral Hygiene of Children 7-12 Years Old at SDN Baletbaru Jember - Lusi Hidayati; Dwi Warna Aju Fatmawati; Suhartini Suhartini; Agustin Wulan Suci Dharmayanti (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2022)
Dental caries is the most common dental and oral health problem experienced by school-age children aged 7-12 years. Dental and oral care behavior is essential in determining individual health status, especially oral health and the level of dental caries. Since the pandemic, SDN Balletbaru never provided counseling and assistance in maintaining oral health. However, since the pandemic, there has never been any assistance regarding dental and oral health maintenance. Based on this, the researchers wanted to examine the relationship between dental caries and the level of oral hygiene of children aged 7-12 years at SDN Balletbaru Jember. This descriptive research was carried out on the students of SDN Balletbaru, Jember Regency, aged 7-12 years. This research was conducted by examining OHI-s, DMF-T, and def-t. The results showed a relationship between oral hygiene, age, sex, and dental caries (R 0.5). In conclusion, there was a relationship between dental caries and the level of oral hygiene of children aged 7-12 years at SDN Balletbaru. Therefore, improving oral hygiene is necessary to promote and prevent dental caries. In order to make this effort a success, coordination and cooperation from all parties are needed, namely the students themselves, parents, teachers, and health workers